1997
DOI: 10.1080/02688699746249
|View full text |Cite
|
Sign up to set email alerts
|

Effects of photodynamic therapy on glioma spheroids

Abstract: The present study describes the sensitivity of glioma cells to a haematoporphyrin derivative (Photosan-3) under laser activation (argon-pumped dye laser). The effects of photodynamic therapy (PDT) on cell growth, directional migration and cell invasion were investigated on two human glioma cell lines (GaMg and U-251 Mg). The directional cell migration and spheroid growth was determined for both cell lines exposed to increasing laser energy output (15-35J/cm2) with concentrations of 5 and 7 micrograms/ml of Pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Type I reactions involve a direct interaction between the photoexcited dye and cellular oxygen resulting in the production of ROS. However, in Type II reactions, singlet oxygen ( 1 O 2 ) is formed as a result of energy transfer between the photoexcited PS and oxygen ( 100 , 101 ). Both types of reactions can occur simultaneously, and which one prevails depends, among others, on the type, dose and physicochemical properties of the PS used ( 102 ).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Type I reactions involve a direct interaction between the photoexcited dye and cellular oxygen resulting in the production of ROS. However, in Type II reactions, singlet oxygen ( 1 O 2 ) is formed as a result of energy transfer between the photoexcited PS and oxygen ( 100 , 101 ). Both types of reactions can occur simultaneously, and which one prevails depends, among others, on the type, dose and physicochemical properties of the PS used ( 102 ).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…normal cerebral tissue markedly increases GBM cell invasion in nude mice, and that glioma cell invasion correlates with activation of a disintegrin metalloprotease domain 17 (ADAM17)-EGFR-PI3K-Akt pathway(Zhenga et al, 2008). Furthermore, PDT decreased the glioma spheroids cell migration and growth capacity, but these spheroids showed the ability for invasion when confronted with normal brain cells aggregated in vivo(Terzis et al, 1997).Peritumoral edema of glioma tumors is characteristic during the invasive growth and recurrence of glioma. The gene products generated from the cerebral edema promote the transport of tumor cells, water, macromolecules, and plasma through the basement membranes of vessel walls to the peritumoral region.…”
mentioning
confidence: 90%
“…This observation has led to greater study of tumors in 3D, as it is closer to in situ growth [8-11] even though it lacks many of the supporting extracellular systems (e.g., endothelial cells and capillaries, supporting matrices, cytokines, etc.). In addition, it has been observed that cancer cell lines grown in 2D and 3D culture respond differently to radiation and cytotoxic drugs [12-14]. Why do cell lines exhibit this differential behavior?…”
Section: Introductionmentioning
confidence: 99%